1995
DOI: 10.1136/bmj.311.7003.471
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking, tar yields, and non-fatal myocardial infarction: 14000 cases and 32000 controls in the United Kingdom

Abstract: The present study indicates that the imminent change of tar yields in the European Union to comply with an upper limit of 12 mg/cigarette will not increase (and may somewhat decrease) the incidence of myocardial infarction, unless they indirectly help perpetuate tobacco use. Even low tar cigarettes still greatly increase rates of myocardial infarction, however, especially among people in their 30s, 40s, and 50s, and far more risk is avoided by not smoking than by changing from one type of cigarette to another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
79
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(96 citation statements)
references
References 22 publications
13
79
0
4
Order By: Relevance
“…The association was stronger in younger individuals than in older individuals. These results were consistent with those of previous studies, which demonstrated that the effect of most cardiovascular risk factors on cardiovascular diseases was stronger in younger than in older individuals (39,40). The effect of H. pylori infection on CAD This meta-analysis demonstrated that H. pylori infection was associated with the risk of CAD.…”
Section: Discussionsupporting
confidence: 92%
“…The association was stronger in younger individuals than in older individuals. These results were consistent with those of previous studies, which demonstrated that the effect of most cardiovascular risk factors on cardiovascular diseases was stronger in younger than in older individuals (39,40). The effect of H. pylori infection on CAD This meta-analysis demonstrated that H. pylori infection was associated with the risk of CAD.…”
Section: Discussionsupporting
confidence: 92%
“…The importance of modifying risk factors is supported by data from randomized trials or persuasive evidence of causality from observational studies. [21][22][23][24][25][26] We and other investigators showed that a pill that combines a statin, antihypertensive therapy, and aspirin together with avoidance of smoking, could potentially reduce the patient risk of developing AMI in Japan. 27,28 Lifestyle modification has been shown to be important in other countries for reducing the risk of AMI, and the present study suggests that lifestyle modification is also important in Japanese men and women of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…After adjustment for current smoking, as defined by serum cotinine, 9 the risks of lung cancer associated with IgG and IgA antibodies and immune complexes to C. pneumoniae were moderately elevated risk of female lung cancer (OR ϭ 1.7, 1.6 and 1.8, respectively, Table I). With the alternative cutoff levels, the point estimates slightly increased (OR ϭ 2.1, 2.1 and 2.2) and all reached statistical significance (Table I).…”
Section: Dear Sirmentioning
confidence: 99%